Advanced applications of current conveyors - Rajput, S. S.; Jamuar, Sudhanshu Shekhar (2002)
Current conveyors (CCs) are replacing op amps in almost all analog signal-processing applications. The current mode architecture of CCs is particularly suitable for low voltage operations and high frequency applications. Another feature of CCs is that they can easily be reconfigured into another current mode Structure. A number of advanced applications of CCs in development of current mode analog circuit structures are presented in this paper. The structures described can be implemented in CMOS technology.